Cevap :
y-x=1 ise x y den küçük
olduğuna göre
x-y negatif mutlak değerden işaretleri tersi çıkar
y-(-x+y)=2
y+x-y=2
y ler gider
x = 2 olur
en başa geldiğimizde
y-x =1
y-2=1 ise y=3 olur
x+y =?
2+3=5
cevap 5
![Görseli göster Sultan3562](https://tr-static.eodev.com/files/d59/d9556ac9561b99f1bc622b68ed10423c.jpg)
y-x=1 ise x y den küçük
olduğuna göre
x-y negatif mutlak değerden işaretleri tersi çıkar
y-(-x+y)=2
y+x-y=2
y ler gider
x = 2 olur
en başa geldiğimizde
y-x =1
y-2=1 ise y=3 olur
x+y =?
2+3=5
cevap 5